The Development of a Technique for Sensitizing Cells of Various Origins for Biotechnological Purposes - Oleshkevich, Anna; Yarygina, Elena (KnE Life Sciences, 2022)
The functional activity stimulation of cell cultures was tested in MDBK cell culture, photobacteria AliivibriofischeriandHalobacteriumhalobium. Theaim of the investigation was to increase the ”yield” of the cells using an environmentallysafe stimulant and membrane-tropic agent that isalso safe for the experimenter. Ultrasonicwaves were used.Experimental ultrasonic exposure varied within the following limits: time from 1 to 300 sec, SATA-intensity of 0.01–2.0 W/cm2, generation frequency of 0.88 or 2.64 MHz, standing or traveling wave. The modulation frequency range was within 0.1–150 Hz. The devices used were: UST-1-01F, UST-5 and UST1.02C. The modulating generators were G3–112 and CP–110.Stimulation of MDBK cell growth was initiated by US-intensity of 0.03–0.05 W/cm2 , with an exposure of 5–30 sec.Exposure to ultrasound with an intensity of 0.2–0.4 W/cm2 (for 3 min) had a stimulating effect on bioluminescence and was associated with an increase in the growth rate ofA. fischeri. The findings indicated that 0.4 W/cm2ultrasonic intensity and modulation frequencies from 0.25 to 0.7 Hz can stimulate the growth of archaea.It was revealed that the maximum proliferation index in all cases of stimulant application was noted in cultures with minimal initial proliferative activity in the control.The authors expect thatthese results on the possibilities of acoustic continuous and modulated waves can be applied for biotechnological purposes to develop a new biotechnological method. Keywords: cell culture, ultrasound, proliferation, stimulation